Diagnosis of the free fair: a case study in São Domingos do Prata, Minas Gerais (Research, Society and Development, 2020)
This paper aims to identify the problems and difficulties faced by the fairgrounds and consumers of the free market of São Domingos do Prata. To do so, we sought to understand the profile and behavior of consumers from different social classes, as well as the profile, characteristics and perceptions of marketers, in relation to the fair. A non-probabilistic, descriptive survey was carried out for accessibility, with the application of 51 semi-structured questionnaires, using the survey. Semi-structured interviews were also held with the 18 marketers. The results showed that consumers visit the fair in search of better quality natural products, more affordable prices and the appreciation of small producers. The organization and location of the fair, days of operation and public support stand out as dysfunctions and problems reported by the fair.